2004
DOI: 10.1007/s00213-003-1697-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphine and naltrexone on impulsive decision making in rats

Abstract: These results suggested that the direct effects of MOR may contribute to the high level of impulsive behavior seen among opiate users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
64
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 42 publications
(45 reference statements)
14
64
4
Order By: Relevance
“…Effects of 0.5 mg/kg amphetamine, intracranial naloxone into the NAc shell and NAc core subregions and their combination, or intracranial morphine into the NAc shell and NAc core subregions on measures of attentional function, compulsivity, and motivation in the 5-CSRTT receptors would be expected to potentiate rather than reduce amphetamineinduced DA release and subsequent impulsive decisions. Interestingly, there is ample evidence linking the opioid system, particularly -opioid receptors, to regulation of impulsive decision making (Kieres et al, 2004;Mitchell et al, 2007;Boettiger et al, 2009;Love et al, 2009;Pattij et al, 2009). It can therefore be concluded that (1) psychostimulants alter impulsive choice via opioid-independent mechanisms and (2) opioids may modify this behavior via distinct neuronal mechanisms.…”
Section: Opioids Amphetamine and Impulsive Choicementioning
confidence: 99%
See 1 more Smart Citation
“…Effects of 0.5 mg/kg amphetamine, intracranial naloxone into the NAc shell and NAc core subregions and their combination, or intracranial morphine into the NAc shell and NAc core subregions on measures of attentional function, compulsivity, and motivation in the 5-CSRTT receptors would be expected to potentiate rather than reduce amphetamineinduced DA release and subsequent impulsive decisions. Interestingly, there is ample evidence linking the opioid system, particularly -opioid receptors, to regulation of impulsive decision making (Kieres et al, 2004;Mitchell et al, 2007;Boettiger et al, 2009;Love et al, 2009;Pattij et al, 2009). It can therefore be concluded that (1) psychostimulants alter impulsive choice via opioid-independent mechanisms and (2) opioids may modify this behavior via distinct neuronal mechanisms.…”
Section: Opioids Amphetamine and Impulsive Choicementioning
confidence: 99%
“…Although the effects of amphetamine on impulsivity depend on enhanced dopamine (DA) transmission Robbins, 1987, 1989;Winstanley et al, 2003Winstanley et al, , 2005van Gaalen et al, 2006bvan Gaalen et al, , 2009Pattij et al, 2007), other neurotransmitter systems may also play crucial roles in regulating impulsive behavior, including endogenous opioid systems (Madden et al, 1997;Kieres et al, 2004;Mitchell et al, 2007;Boettiger et al, 2009;Love et al, 2009;Olmstead et al, 2009;Pattij et al, 2009;Zacny and de Wit, 2009). Indeed, there is ample evidence showing that amphetamine activates endogenous opioid systems McGinty, 1995, 1996;Olive et al, 2001;Gonzalez-Nicolini et al, 2003), and the effects of amphetamine on DA release and behavioral measures including locomotion, reward, and amphetamine-induced rein-statement of amphetamine seeking involve opioid transmission (Trujillo et al, 1991;Hooks et al, 1992;Schad et al, 1995;Jayaram-Lindström et al, 2004Häggkvist et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the modulation of inhibitory control per se, however, opioids have received comparatively little attention. A small number of systemic pharmacology and gene knockout studies have shown that μ-opioid receptor (μOR) signaling promotes impulsivity; however, the brain sites underlying this effect are not fully known (Kieres et al, 2004;Mahoney et al, 2013;Olmstead et al, 2009;Pattij et al, 2009). To date, the possibility that endogenous opioids act within frontal cortex to modulate (or provoke) impulsive reward-seeking action has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by animal studies that have shown NTX to be effective at decreasing impulsive choice bias. For example, in rats, NTX reverses a morphine induced increase in preference for small immediate rewards over larger delayed rewards (Kieres et al, 2004). Moreover, in humans, NTX attenuates a variety of impulse disorders, including pathological gambling (Kim et al, 2001), binge eating in bulimics (Marrazzi et al, 1995), compulsive sexual behavior (Raymond et al, 2002), self-injurious behavior (Symons et al, 2004), and kleptomania (Grant, 2005).…”
Section: Introductionmentioning
confidence: 99%